Serum Tsukushi level is negatively associated with cholesterol efflux capacity in metabolic dysfunction-associated steatotic liver disease: a cross-sectional study - Sum Lam; David T. W. Lui; Carol H. Y. Fong; Ying Wong; Sammy W. M. Shiu; Karen S. L. Lam; Lung-Yi Mak; Man-Fung Yuen; Chi-Ho Lee; Kathryn Choon-Beng Tan (Scientific Reports)
Abstract Background Tsukushi (TSK), a recently identified hepatokine, has been shown to affect systemic cholesterol homeostasis and reduce HDL cholesterol (HDL-C) in murine studies. We have investigated whether TSK is associated with HDL-C and HDL function in subjects with and without MASLD. Methods Vibration-controlled transient elastography was performed in 896 subjects (63.1% with type 2 diabetes (T2D)). The presence of MASLD was defined as controlled attenuation parameter ≥ 248 dB/m with at least one cardiometabolic criteria. Serum TSK levels were measured by ELISA. Cholesterol efflux capacity (CEC), an indicator of HDL function, was determined by measuring the efflux of tritiated cholesterol from RAW264.7 macrophages to apolipoprotein B-depleted serum. Results Serum TSK levels were higher in subjects with MASLD than those without (p < 0.001) whereas plasma HDL-C and CEC (18.4 ± 5.2% versus 20.6 ± 6.2% respectively, p < 0.001) was significantly lower in MASLD subjects irrespective of the status of diabetes. Subgroup analysis stratified by the T2D and MASLD status showed that non-diabetic MASLD subjects had reduced CEC (p < 0.001). Interestingly, CEC was also reduced in diabetic subjects without MASLD (p < 0.001) suggesting that the status of T2D alone could affect the CEC of HDL, and the greatest degree of reduction in CEC was seen in subjects with both T2D and MASLD (p < 0.001). On multivariable linear regression analyses, TSK and HDL-C were significant independent determinants of CEC in both subjects with and without T2D after adjusting for hepatic steatosis and other potential confounders. Conclusion Elevated TSK level was negatively associated with HDL-C and CEC in subjects with MASLD, and the presence of T2D further exacerbated the reduction in CEC.